Comparison of Hydoponic System Between Wick Design With NFT Design on Kangkung Growth Ipomoea aquatica - Ridha Nirmalasari; Fitriana - Fitriana (Jurnal Ilmu Alam dan Lingkungan, 2018)
This study aims to find out the comparison of the growth on wick and NFTdesigns and to know the hydroponic design more effective between the two systems tooptimize the growth of kangkung plants. The method used is quantitative experiment witht-Test test data analysis: Paired Two Sample For Means (two paired samples). The studywas conducted for two weeks with one week of seeding and one week of measurement.The parameters observed were number of leaves, leaf length, leaf width, and stem height.The results showed that the growth of kangkung plants in hydroponic wick design isbetter than the NFT design. The growth on wick design can be said better because in thisdesign each hydroponic place is only filled by one kangkung plant so that the absorptionof nutrient solution can occur more optimally. This study proves that there aredifferences in the growth of kangkung plants in wick and NFT design.